Mycosis fungoides and Sézary syndrome - Ieva Saulite; Antonio Cozzio; Emmanuella Guenova (healthbook TIMES. Oncology Hematology)
Mycosis fungoides (MF) and Sézary syndrome (SS) are two subgroups of cutaneous T-cell lymphomas (CTCL), which belong to the extranodal non-Hodgkin lymphomas. These are rare diseases whose etiology is still not fully understood. Regarding pathogenesis, mycosis fungoides and Sézary syndrome derive from different T-helper cell types and are therefore considered two separate entities according to the current concept. Mycosis fungoides is clinically characterized by patch, plaque and tumor stages, although the disease can also manifest as erythroderma. Sézary syndrome is characterized by the presence of erythroderma, defined as redness of the skin covering >80% of the total body surface area. In the blood count of patients with mycosis fungoides, a T-lymphocytosis, especially with CD4-positive cells, can only be observed in advanced stage IV. One of the typical histological findings is an epidermotropic infiltrate of atypical, CD4-positive T-cells. Characteristic features of Sézary syndrome include atypical T lymphocytes (Sézary cells) in the blood and skin infiltrate. The diagnosis of both mycosis fungoides and Sézary syndrome is based on clinical, histological and hematological examinations as well as imaging techniques. Staging is based on the tumor-node-metastasis-blood (TNMB) classification and is a crucial factor in determining the prognosis. The treatment of mycosis fungoides and Sézary syndrome is carried out according to the stage, whereby local therapies such as UVB phototherapy are used as well as systemic forms of treatment, and in addition, in recent years, targeted therapies have increasingly become part of everyday clinical practice.